Photocatalytic degradation of reactive dye RED-3BA in aqueous TiO2 suspension under UV-visible light. (2005) - Dung, Nguyen Thi; Van Khoa, Nguyen; Herrmann, Jean-Marie
Abstract : The photo-catalytic degradation efficiency of several commercial titania powders (Degussa P-25 and Ishihara Sangyo ST-01) and ofTiO 2 supported on diatomite were investigated in the degradation of a reactive dye (RED-3BA) under UV-Visible light. The observed rate constant for Degussa P-25 was found to be higher than that achieved by using Ishihara Sangyo ST-01 (k obs = 3.3 × 10 − 2 min − 1 for Degussa P-25 and 4 × 10 − 4 min − 1 for Ishihara Sangyo ST-01). This could be related to the amount of basic hydroxyl groups on the surface ofTiO 2 particles as shown in the IR spectra.TiO 2 Degussa P-25 supported on diatomite was prepared by dip-coating method. The photo-catalytic activity of supportedTiO 2 was twice smaller thanTiO 2 Degussa P-25 (k p-25 = 3.3 × 10 − 2 min − 1 ;k p25/diatomite = 1.6 × 10 − 2 min − 1 ). The higher surface areas of ST-01 and theTiO 2 /diatomite could not lead to a higher degradation rate and to a higher degree of mineralization butTiO 2 /diatomite could be separated more promptly and more easily from the solution. The effect of pH was investigated in the range 4–9. Acidic (pH = 4) medium was found to favor the adsorption and degradation rate with P-25 particles.